Faktor-Faktor Yang Berhubungan Dengan Penggunaan Jarum Suntik Bergantian Diantara Pengguna Napza Suntik Di Kota Semarang - Heri Winarno; Antono Suryoputro; Zahroh Shaluhiyah (Master Program of Health Promotion Faculty of Public Health Diponegoro University, 2008)
Background : The cumulative case of Acquired Immunodeficiency Syndrome (AIDS) in Indonesia by the year 2007 was reported transmitted mostly through drug injection. We understand that injecting drug users facing a high risk to be infected by HIV / acquired immunodeficiency syndrome from two different source of transmission. First, through needlesharing and second through unsafe sexual intercourse this usually came along the drug use. This study is aimed to analyze factors related to needle sharing practise among injecting drug users in Semarang City.Method : This was an explanatory study, employed a survey method and cross sectional as the research design. Target population in this research was all injecting drug users in Semarang City. There were 75 respondents from 56 minimum sample size required involved in this research, selected by applying snowball sampling technique. Chi – Square analysis and biserial correlation were applied to measure bivariate correlation and logistic regression was used for multivariate analysis.Results : Out of the 75 injecting drug users, 34,7% IDUs experience needle sharing during the last six month. It was found that needle sharing associated with knowledge of HIV/AIDS, perceived barrier of using sterile needle, low self-efficacy, needle exchange program use, availability of sterile needles, voluntary counseling and testing, and peer norms. Needle sharing was also associated with frequency of IDUs met outreach worker, but not associated with perceived susceptibility of HIV, perceived severity of AIDS, and perceived benefit of using sterile needle. Logistic regression found needle sharing to be more likely among injecting drug users have less knowledge of HIV/AIDS and low self-efficacy.Key words : needle sharing practise, injecting drug users, HIV/AIDS